Issues in remote laboratory developments for biomedical engineering education - Barros, C. (2013)
In engineering and sciences education, the laboratorial experiment is an important component of the learning process. The recurrent or intensive use of laboratories leads to the improvement of students’ skills. Nevertheless, the need of laboratorial practice has led to the development of innovative solutions: the remote labs. This work intends to discuss the preliminaries developments of a new remote laboratory for biomedical engineering courses: Remote Physiological System (RePhyS) laboratory. LabVIEW was the tool used for both the device handling (control and configuration) and the web platform’s deployment. However it could be incompatible with some web browsers. To overcome this limitation, the team explores news user-side solutions. With this innovative teaching/learning tool, the students should be able to recognize the biosignals and the acquisition methods in an intuitive and easy way, allowing them to improve their knowledge.